Mediasi Sebagai Pilar Ketahanan Keluarga dalam Penyelesaian Sengketa Rumah Tangga - Febby Ansah Tri Pamungkas; Musleh Harry (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The family constitutes a fundamental foundation of social resilience; however, the dynamics of modern life have made domestic conflicts increasingly complex and unavoidable. Litigation-based dispute resolution often adopts an adversarial, win lose approach that may intensify relational tensions and overlook emotional dimensions as well as children’s best interests. This article examines mediation as a humane and relationally oriented mechanism for resolving domestic disputes and analyzes its relevance in strengthening family resilience. Employing a normative juridical approach, this study reviews statutory regulations, mediation frameworks, and scholarly perspectives on family law. The findings indicate that mediation promotes dialogue, mutual agreement, and shared responsibility among the parties, enabling conflicts to be managed constructively and with dignity. Although its implementation faces challenges such as limited legal awareness and mediator capacity, mediation demonstrates significant potential as a strategic pillar for enhancing family resilience and fostering a more just, sustainable, and human-centered family law system.Keywords: Mediation; Family Resilience; Domestic Disputes; Family Law